Condiments before Claudius: new plant foods at the Late Iron Age oppidum at Silchester, UK - Lodwick, L (Springer-Verlag, 2013)
Our understanding of the introduction and adoption of new plant foods in Roman Britain is currently limited by a lack of data from a group of Late Iron Age settlements commonly referred to as oppida (large pre-Roman towns). This paper presents the first evidence of several imported plant foods from Late Iron Age Britain in the form of waterlogged plant remains from the oppidum at Silchester. These were recovered from the basal contexts of two wells, dated to the early first century A.D. One olive stone and several seeds of celery, coriander and dill were identified. The results are compared to archaeobotanical data from elsewhere in Britain and northwestern Europe, demonstrating that Silchester is part of the wider phenomenon of the adoption of new flavourings and fruits in Late Iron Age Europe.